Egy migrációgazdaság lehetséges útjáról: Lapszéli jegyzetek – emlékeztetőül - A. Gergely, András (Afrika Tanulmányok / Hungarian Journal of African Studies, 2022)
This short review piece gives a summary of Zsuzsánna Biedermann’s academic works, commemorating her contributions to Hungarian African Studies and scholarship on international migration as well as development economics.